FAKTOR KEBUTUHAN KONSUMEN DALAM MEMBELI PRODUK REUSE - Liris Windyaningrum, Theresia (Widya Warta, 2012)
This article examines the factors that become the needs of consumers who once used the reused product. 8.50 LISREL program was used as a means of structural equation modeling analysis of the conceptual framework of research. The results showed that consumers of this category had the possibility to buy reused product if it had the reliability that might operate inaccordance with its function, thus it does not matter if the price of reused product may equal to the price of new product. In addition, a guaranteed replacement of the damaged components during the warranty period and the ease of getting reused product on the market as well as innovation in the reused product continually pursued by the manufacturer would be a prerequisite factor in the willingness of consumers to buy reused product. On the other hand, a guarantee of reused product factually didn’t reduce the anxiety of consumers to buy reused product, neither did the reputation of a company that had not been agreed upon by consumers of this category as supporting quality of reused product.